Development of polyclonal antibody against clenbuterol for immunoassay application - A. Talib, Nurul Ain; Salam, Faridah; Sulaiman, Yusran (MDPI, 2018)
Development of an immunoassay for clenbuterol (CLB) detection required an anti-CLB antibody as an important bioreceptor. In this study, we report our work on production and purification of a rabbit-derived polyclonal anti-CLB antibody. The antibody was then purified by nProtein A Sepharose affinity column and the antibody purity was confirmed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis. The activities of purified antibody were evaluated based on high antibody titer determined from enzyme-linked immunosorbent assay (ELISA). The sensitivity and selectivity of this antibody was evaluated and exhibits negligible cross-reactivity to antibiotics other than β-agonist families. Evaluation of the antibody as bioreceptor in immunoassay was performed using direct competitive ELISA and exhibited linear calibration plot (R2 = 0.9484). The antibody was used to detect the content of CLB in spiked milk samples and the recovery of more than 92% indicating significant performance as bioreceptor for the development of a rapid and simple immunoassay.